OPTIMIZING THE CONTENT OF TEACHING CHINESE IN THE MODERN EDUCATIONAL PARADIGM - Shasaidova, Lola (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
Today, the relevance of optimizing the content of Chinese language teaching is higher than ever. The current stage of the development of the educational system is characterized by an increase in the volume of information, its improvement, and constant updating. Today, educational standards, the content of curricula and textbooks, and the technologies used in education are changing. At the same time, the amount of information that the learner needs to know and its level of complexity is also increasing. The educational system should always be ready for such changes and updates. The article discusses current trends and problems of optimizing the educational process, which would, on the one hand, ensure high-quality assimilation of educational material, and on the other hand, would not require an increase in time and financial costs, nervous tension, strength and health of the participants in the educational process. Optimizing the educational process requires a conscious choice of the most optimal alternative of approaches and methods that provide maximum efficiency in the current conditions to solve the set tasks. The accumulated experience of well-known linguodidactics and pedagogues was analyzed to justify the concept of optimization. The ways and principles of optimizing the content of Chinese language education in the modern educational paradigm were considered.